Response of mice and ferrets to a monovalent influenza A (H7N9) split vaccine. - Yueqiang Duan; Hongjing Gu; Rui Chen; Zhongpeng Zhao; Liangyan Zhang; Li Xing; Chengcai Lai; Peirui Zhang; Zhiwei Li; Keming Zhang; Zhouhai Wang; Shaogeng Zhang; et al. (PLoS ONE, 2014)
In early spring 2013, the emergence of the influenza A (H7N9) virus in humans in Eastern China raised concerns of a new influenza pandemic. Development of a safe and effective H7N9 influenza vaccine is urgently needed. To this end, we first synthesized the hemagglutinin (HA) and neuraminidase (NA) genes of the influenza A (H7N9) virus A/AnHui/1/2013. Using reverse genetics, we rescued a reassortant virus (H7N9/PR8) that contained the HA and NA genes from wild-type H7N9 and six genes encoding internal proteins from the A/Puerto Rico/8/34 (PR8) virus. Next, the pathogenicity of the reassortant virus was evaluated both in vivo and in vitro. We found that the virus was non-pathogenic in mice and was stable after serial passaging in eggs. Furthermore, we found that a monovalent influenza A (H7N9) split vaccine prepared from the virus was immunogenic in mice and ferrets. When given intramuscularly, the vaccine (two doses of at least 15-µg) completely protected mice from normally lethal wild-type H7N9 virus challenge. In summary, our H7N9 vaccine, developed over a short time, is a potential candidate for further clinical evaluation and human use.